Sistem Pendukung Keputusan Pemilihan Mahasiswa Penerima Bantuan Uang Kuliah Tunggal Menggunakan Metode Simple Additive Weighting (SAW) - Nur Wulandari; Nurul Izzah Hadiana; Mesran Mesran; Rohmat Indra Borman; Agus Perdana Windarto (ADA Research Center, 2023)
Single Tuition Assistance (UKT) is a government program to help students who are academically capable and economically disadvantaged. The form of UKT assistance provided by the government to recipient students is tuition assistance which is transferred directly to the university's account. This assistance is intended for underprivileged students. In order for the provision of UKT assistance to be right on target, the selection in receiving aid must be better and objective in accordance with predetermined criteria. However, universities often face several problems in the selection process, which is carried out in stages so that it takes quite a long time. Therefore, a decision support system is needed as a solution to these problems by applying the Simple Additive Weighting (SAW) method. The test results obtained that the best alternative that was considered worthy as a student receiving UKT assistance was in alternative A4 on behalf of Khairunnisa which resulted in the best preference value of 0.8865 as the first rank.